George Perry interviewed by Mark St Leon in Mark St Leon circus collection (1985-1988) - Perry, George, 1896-; St. Leon, Mark, 1952- (1987)
Perry speaks of his family circus background; Eroni Brothers' Circus beginnings his early training; learning wirewalking; practising with Con Colleano; Colleano's father's boxing show; establishment of Perry Brothers' Circus; Colleano family; Colleano's wire movements; Mary Sole, other female wirewalkers; St Leon family recollections; Ashton's history; Jack Zinga; May Wirth; Vera & Clarence Bruce; non-European circus performers; Dallinger wagons; Dummy Perry; religious education; old Mrs Ashton; circus size; music; Colleano's act; salaries; travelling with Eroni's; circus food; meeting other circuses on the road; Walduck's circus; Walter St Leon circus; tent; digging the ring; Bostock & Wombell's vaudeville show; Atkinson's Wild West Show; Eroni's & Perry's amalgamations; Hyland's Circus; other small circuses; James Ashton; circus language; Colleano's Aboriginal background; change in circus life; riding acts; other St Leons acts.
Edna Perry? is also present at the interview.
Recorded at Maribyrnong, Vic. in June and July 1987.
Digital master available
Transcript available (typescript, 75 leaves)
Keywords: Perry, George, -- 1896- -- Interviews; Colleano, Con, -- 1899-1973.; Perry Bros. Circus -- History; Eroni Brothers' Circus -- History; Circus performers -- Australia -- Interviews; Circus -- Australia -- History